The Use of Rapid Application Development (RAD) Model in the Development of Raw Material Inventory Information System - Hidayati, Nur (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2025)
In a company, there are several areas it manages, such as sales, purchases, inventory, marketing, production, and many other fields. Inventory, which is one of those areas, becomes a crucial center in the sustainability of the company's operations. This is because inventory has a relationship with sales and purchases, or is related to incoming and outgoing goods. Therefore, special attention is needed in this area of inventory. Inventory is not only related to goods but also to raw materials, depending on the type of company being run. In the inventory of raw materials specifically, it is essential to clearly understand the raw materials available in the company so that it can meet the company's needs in producing goods. To obtain this clear information, good information systems are certainly required. However, in reality, there are still many companies that use a manual system in managing their inventory data. This can obviously lead to several problems such as the information obtained regarding the final condition of the raw materials not being updated properly due to recording errors made on the incoming and outgoing raw materials. This condition results in the preparation of inventory reports being incorrect, thus making the information provided inaccurate. If this continues, it will negatively impact the company's survival. The company may incur significant losses and be unable to compete with other companies. Therefore, such companies need the development of a system that will transform from a manual system to a computerized system. With the hope of resolving the issues faced. In the process of developing the system, it is also necessary to choose the right model, such as the Rapid Application Development model. Because in this model, the existing stages can be carried out clearly and systematically and can have a short time estimate in the development of the system. The final result of this system development can be an inventory application that can be used to assist in managing its inventory data.